1.Wykonaj mnozenie
a) x(3x2 + 2x - 9)=
b) 2w (4w3 + 10w2 - 9w - 2)
c) 3y2(5 - 6y2+ 7y3)
d) -4k(- kl - k2 - l2 +6)
e) 2,4x2 (-3y2 - 4xy +10x2)
f) -2 1/5tw (3/11t2 - 4/11w2 - 5/11tw)
g) 106 (6 to potega) * (108x4 - 104x3 (4 to potega)
h) -0,125a(-8b+1/8a2 - 32 a3b3


2.Wykonaj mnozenie
a) 5(x - 2) + 6(x-3)
b) 7(x+6) + 8(x-4) - 9(x+1)
c) 8(3x-2) - 6(-2x + 4) - 2(9x -6)
d) 6x(3-x) + 4x(5 - 2x)
e)x3(x2-1) - x2(x3-1)
f) -2(x3 + 2x2-x) - x(-2x2+4) + 1/2x(6x+8)

3.Wykonaj dzielenie

a) (10z2 + 20z + 30) : 10
b) (56ab + 48a2 - 24b2) : (-8)
c) (-6t2 - 3t - 9) : 2/3
d) (5mp + 6m - 2p) : (-o,1)

prosze pomozcie nie rozumiem tego a to na jutro

2

Odpowiedzi

2010-04-13T22:59:12+02:00
A) x(3x2 + 2x - 9)= 3x3+2x2-9x
b) 2w (4w3 + 10w2 - 9w - 2)= 8w4+20w3-18w2-4w
c) 3y2(5 - 6y2+ 7y3)=15y2-18y4+21y5
d) -4k(- kl - k2 - l2 +6)=4k2l+4k3+4kl2-24k
e) 2,4x2 (-3y2 - 4xy +10x2)= 7,2x2y2-9,6x3y+24x4
f) -2 1/5tw (3/11t2 - 4/11w2 - 5/11tw)=-9/55t3w+24/55tw3+6/11t2w2
h) -0,125a(-8b+1/8a2 - 32 a3b3=1ab-125/800a3+4a4b3

a) 5(x - 2) + 6(x-3)=5x-10+6x-18=11x-28
b) 7(x+6) + 8(x-4) - 9(x+1)=7x+42+8x-32-9x-9=6x+1
c) 8(3x-2) - 6(-2x + 4) - 2(9x -6)=24x-16+12x-24-18x+12=18x-28
d) 6x(3-x) + 4x(5 - 2x)=18x-6x2+20x-8x2=-14x2+38x
e)x3(x2-1) - x2(x3-1)=x5-x3-x5-x3=-x6
f) -2(x3 + 2x2-x) - x(-2x2+4) + 1/2x(6x+8)=-2x3-4x2+2x+2x3-4x+3x2+4x=x2+2x

a) (10z2 + 20z + 30) : 10=z2+2z+3
b) (56ab + 48a2 - 24b2) : (-8)=-7ab-(-6a2)+3b2
c) (-6t2 - 3t - 9) : 2/3=-9t2-4.5t-13.5
d) (5mp + 6m - 2p) : (-o,1)=-50mp-(-60m)+20p
Najlepsza Odpowiedź!
2010-04-13T23:12:39+02:00
1.Wykonaj mnozenie
a) x(3x2 + 2x - 9)=3x³+2x²-9x
b) 2w (4w3 + 10w2 - 9w - 2)=8w⁴+20w³-18w²-4w
c) 3y2(5 - 6y2+ 7y3)=15y²-18y⁴+21y⁵
d) -4k(- kl - k2 - l2 +6)=4k²l+4k³+4kl²-24k
e) 2,4x2 (-3y2 - 4xy +10x2)=-7,2x²y²-9,6x³y+24x⁴
f) -2 1/5tw (3/11t2 - 4/11w2 - 5/11tw)=-33/55t³w+44/55tw³+t²w²
g) 106 (6 to potega) * (108x4 - 104x3 (4 to potega)=10¹⁴x⁴-10¹⁰x³
h) -0,125a(-8b+1/8a2 - 32 a3b3=ab-0,016a³-4a²(-0,375)ab(-0,375)a

zad. 2
a) 5(x - 2) + 6(x-3)=5x-10+6x-18=11x-28
b) 7(x+6) + 8(x-4) - 9(x+1)=7x+42+8x-32-9x-9=6x+1
c) 8(3x-2) - 6(-2x + 4) - 2(9x -6)=24x-16+12x-24-18x+12=18x-28
d) 6x(3-x) + 4x(5 - 2x)=18x-6x²+20x-8x²=-14x²+38x
e)x3(x2-1) - x2(x3-1)=x⁵-x³-x⁵+x²=x²-x³
f) -2(x3 + 2x2-x) - x(-2x2+4) + 1/2x(6x+8)= -2x³-4x²+2x+2x³-4x+3x²+4x=-x²+2x

3.Wykonaj dzielenie

a) (10z2 + 20z + 30) : 10=z²+2z+3
b) (56ab + 48a2 - 24b2) : (-8)=-7ab-6a²+3b²
c) (-6t2 - 3=t - 9) : 2/3=-9t²-3+⅔/t-13,5
d) (5mp + 6m - 2p) : (-o,1)=-50mp-60m+20p
6 5 6